Comparison between different non-destructive techniques methods to detect and characterize impact damage on composite laminates. (March 2020) - Papa, I; Ricciardi, MR; Antonucci, V; Langella, A; Tirillò, J; Sarasini, F; Pagliarulo, V; Ferraro, P; Lopresto, V
This paper aims to investigate the ability of ultrasonic and electronic speckle pattern interferometry to analyse the low-velocity impact internal damage mechanisms on basalt composite laminates and to provide information on the shape and the extent of the delamination in non-destructive way. Basalt/epoxy composites with different thicknesses have been realised and characterised by mechanical tests to investigate both fibre-dominated (tensile and flexural behaviour) and matrix-dominated properties (interlaminar shear strength). Specimens were impacted at penetration and at increasing energy values, to explore the damage onset and propagation. The results showed that the damage was concentrated under the impactor–material contact point and that the composite with intermediate thickness had the best balance between the different kinds of impact damages: delamination and indentation. Further, a good agreement was found between the overall data obtained by the two non-destructive techniques, confirming the capability of both techniques to examine the composite impact damage.